2020
DOI: 10.3906/tar-1910-33
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of common bean (Phaseolusvulgaris L.) accessions

Abstract: With an annual global production of approximately 25 million tons, the common bean (Phaseolus vulgaris L), a member of the genus Phaseolus, is one of the major protein sources used as food for humans. In this study, it was aimed to investigate the genome size of the common bean genetic resource collection (154 common bean accessions) in Turkey by flow cytometry (FCM) and determine whether geographical variables affected the genome size. In addition, the number and distribution of 5S and 45S ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…The chromosome number in all genotypes was 2n = 2x = 22, confirming several previous results [17,[19][20][21][22][23][24][27][28][29][30]. The MTCL (Mean Total Chromosome Length) recorded in the studied genotypes varied from 15.65 ± 0.99 to 34.24 ± 0.35 micrometers (Table 2), which is almost similar to the previous study on nine genotypes of the common bean, who's MTCL was measured to be between 13.74 and 29.50 micrometers [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The chromosome number in all genotypes was 2n = 2x = 22, confirming several previous results [17,[19][20][21][22][23][24][27][28][29][30]. The MTCL (Mean Total Chromosome Length) recorded in the studied genotypes varied from 15.65 ± 0.99 to 34.24 ± 0.35 micrometers (Table 2), which is almost similar to the previous study on nine genotypes of the common bean, who's MTCL was measured to be between 13.74 and 29.50 micrometers [24].…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained from the current study area similar to some of these results and different from others. This may be due to the use of different methods, internal standards, and accessions or technical problems [42]; in many cases, these changes are related to different geographical and climatic conditions [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study to determine whether geographical variables affected the genome size showed that the cultivars with high DNA content are better adapted to cold or temperate regions, while those with a lower DNA content are well adapted to hot, dry environments. Most of P. vulgaris cultivars were characterized by the mean nuclear DNA content 2C from 1.28 to 1.55 pg2C -1 , and the mean for species was calculated as 1.35 pg2C -1 ( Savas Tuna et al., 2020 ). Castagnaro et al.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques, internal standards, and accessions can account for the differences reported in genome size. The geographical location and distance may also be influential factors ( Wang et al., 2013 ; Savas Tuna et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%